Classification and functional repair and reconstruction of lip and perilabial defects following oncosurgery - CHEN Weiliang (口腔疾病防治)
Defects in the lip and perilabial regions can be caused by lip oncosurgery. Currently, there is a lack of clear classification and principles for repairing and reconstructing the lip and perilabial defects after lip tumor resection surgery. Lip defects are categorized into three types based on their extent by author: partial lip defects, full-thickness lip defects, and full-thickness lip defects with surrounding lip defects. The partial lip defects include four types: labial vermilion defects, labial cutaneous defects, labial mucosal defects, and through-and-through labial defects. There are four types of full-thickness lip defects, including less than half of labial defects, one half of labial defects, subtotal labial defects, and total labial defects. There are three types of full-thickness lip defects with surrounding lip defects, including through-and-through commissure and cheek defects, total labial and nasal defects, and total labial and chin defects. Different types of defects in the lip and perilabial region should be repaired during radical surgery for lip tumors. The methods of repair and reconstruction of lip and perilabial defects include primary closure, skin or mucosal grafting, local flaps, regional flaps, pedicle flaps, free flaps, and allogeneic dermal matrix (ADM). Multiple tissue flaps can also be combined for repair and reconstruction. Among them, the anteriorly based ventral tongue flap is an ideal tissue flap for repairing and reconstructing labial vermilion defects. The Abbe-Estlander flap is a very important technique for repairing and reconstructing lip defects. The combination of bilateral mental neurovascular V-Y island advancement flap and an anteriorly based ventral tongue flap for reconstruction of the total lower lip defect is a reliable and effective method. The Estlander flap, foldable supraclavicular fasciocutaneous island flap, or foldable facial-submental artery island flap can be used to repair the through-and-through labial commissure and cheek defects. Large perilabial defects such as total labial and chin defects or total labial and nasal defects require repair using pectoralis major muscle flaps, trapezius muscle flaps, free tissue flaps, or even a combination of multiple flaps. This article proposes the classification of lip and perilabial defects following oncosurgery and systematically elaborates on the functional repair and reconstruction of the defects, which has certain guiding and promotional application value for clinical practice.